A Literature Review: Risk Factors For Respiratory Arrest - Fitrianti, Fitrianti; Fendy Dwimartyono; Ade Irna (Jurnal EduHealth, 2024)
Cardiopulmonary arrest remains a major public health burden in developed countries. A most of the previous studies, have investigated the increasing problem of respiratory mortality. Stopping breathing is also characterized by disruption of pulmonary gas exchange for more than 5 minutes, which can cause permanent damage to vital organs, especially the brain. The aim of the study was to determine the risk factors for respiratory arrest. Method: search for articles for this narrative review using the keywords respiratory arrest, risk factors for respiratory arrest through websites such as PubMed, Google Scholar, ScienceDirect and Elsevier. Results: Risk factors that generally influence the incidence of respiratory arrest are gender, age, comorbidities, duration of hospitalization, and speed of CPR.